Influence of Silver-Zinc Zeolite Incorporation on Shear Bond Strength of Silicon Cold Cure Soft Liner - Huda Alaa Aldeen Sadeq; Israa Mohammed Hummudi (Journal of Techniques)
Back ground: Reduction of a durable bond to acrylic denture base is the main problem associated with soft liner materials.